2006
DOI: 10.1074/jbc.m603094200
|View full text |Cite
|
Sign up to set email alerts
|

The Constitutive Expression of Anticoagulant Protein S Is Regulated through Multiple Binding Sites for Sp1 and Sp3 Transcription Factors in the Protein S Gene Promoter

Abstract: Protein S (PS) is a vitamin K-dependent plasma protein that inhibits blood coagulation by serving as a nonenzymatic cofactor for activated protein C in the protein C anticoagulant pathway. Low PS levels are a risk factor for the development of deep venous thrombosis. The regulation of PS levels through transcriptional regulation of the PS gene was investigated in this report. A minimal PS gene promoter 370 bp upstream from the translational initiation codon was sufficient for maximal promoter activity in trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 58 publications
7
27
0
Order By: Relevance
“…The luciferase assays suggested that the GC-rich motif at Ϫ172 of the PROS1 promoter plays an important role in E 2 -dependent gene repression. In subsequent EMSAs and DNA pulldown analyses, we observed that Sp1 and Sp3 bound to the GC-rich motif of PROS1, which was consistent with the findings of de Wolf et al (38).…”
Section: Discussionsupporting
confidence: 80%
“…The luciferase assays suggested that the GC-rich motif at Ϫ172 of the PROS1 promoter plays an important role in E 2 -dependent gene repression. In subsequent EMSAs and DNA pulldown analyses, we observed that Sp1 and Sp3 bound to the GC-rich motif of PROS1, which was consistent with the findings of de Wolf et al (38).…”
Section: Discussionsupporting
confidence: 80%
“…36 -38 Recently, constitutive expression of the PROS1 promoter was shown to be regulated mainly by Sp1 in vitro, and to contain binding sites for various other transcription factors such as the hepatocyte-specific forkhead transcription factor FOXA2, which are possibly involved in tissuespecific or induced expression of the PROS1 promoter. 39,40 We confirmed earlier findings that PS is upregulated by IL-6 in cultured HepG2 cells and complemented these with quantitative PS mRNA data thereby identifying the regulatory mechanism as pretranslational. Subsequently, we identified a region in the PS promoter spanning nucleotides 229 to 207 upstream from the translational start that binds STAT3, one of the nuclear messengers of IL-6.…”
supporting
confidence: 77%
“…The generation of PROS1 promoter reporter constructs is described in de Wolf et al 40 PROS1 promoter constructs were mutated at a putative STAT3 binding site by use of the QuikChange XL SiteDirected Mutagenesis kit from Stratagene, with forward primer 5Ј-CCA GCT CCG AAA AGC CGC CTG GTG C TG TCC TTG TTA TCA C-3Јand reverse primer 5Ј-GTG ATA ACA AGG ACA GCA CCA GGC GGC TTT TCG GAG CTG G-3Ј. Successful incorporation of the mutations was confirmed by automated sequencing (Beckman).…”
Section: Plasmidsmentioning
confidence: 99%
“…Protein S is produced in the liver and by endothelial cells (41). Production of both protein S and C4BP in the liver appears to be controlled by inflammatory mediators, including IL-6 (42,43). Levels of protein S are reduced in patients with ischemic stroke (44) and in patients with sepsis (45), possibly via the effects of TNF on endothelial cells (46).…”
Section: Discussionmentioning
confidence: 99%